2013
DOI: 10.1155/2013/757126
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and Antioxidant Effects of Saponarin, Isolated fromGypsophila trichotomaWend. on Paracetamol-Induced Liver Damage in Rats

Abstract: The hepatoprotective potential of saponarin, isolated from Gypsophila trichotoma, was evaluated in vitro/in vivo using a hepatotoxicity model of paracetamol-induced liver injury. In freshly isolated rat hepatocytes, paracetamol (100 μmol) led to a significant decrease in cell viability, increased LDH leakage, decreased levels of cellular GSH, and elevated MDA quantity. Saponarin (60–0.006 μg/mL) preincubation, however, significantly ameliorated paracetamol-induced hepatotoxicity in a concentration-dependent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…This shows that the plasma MDA level can be used as a biomarker for oxidative stress [ 13 ]. The MDA value of the liver tissue was detected to be increased in the group with induced paracetamol toxicity and the values obtained were in line with the results from the recent relevant trials [ 14 16 ]. In our trial, we detected that the increased oxidative stress could be prevented by leptin.…”
Section: Discussionsupporting
confidence: 88%
“…This shows that the plasma MDA level can be used as a biomarker for oxidative stress [ 13 ]. The MDA value of the liver tissue was detected to be increased in the group with induced paracetamol toxicity and the values obtained were in line with the results from the recent relevant trials [ 14 16 ]. In our trial, we detected that the increased oxidative stress could be prevented by leptin.…”
Section: Discussionsupporting
confidence: 88%
“… reported that APAP intoxication raises MDA and decreases GSH levels in rats. Similarly, a statistically significant increase in MDA quantity and depletion in GSH levels have been shown both in vitro and in vivo . Because of the inhibition of lipid peroxidation by the defence mechanisms of the body itself, the reduced lipid peroxidation cannot cause this severe hepatic injury alone.…”
Section: Discussionmentioning
confidence: 98%
“…Silymarin has hepatoprotective properties and is used in treatment of various liver diseases [ 11 ]. Various studies indicate that Silymarin exhibits strong antioxidant activity [ 36 ] and shows protective effects against hepatic toxicity induced by a wide variety of agents by inhibiting lipid peroxidation [ 30 , 37 ]. Higher total phenolic content has been known to contribute to the antioxidant activity of extracts [ 38 ], while antioxidant activity has also been linked to the hepatoprotective effect of some extracts [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%